SIMULATION OF OPTIMAL ANGLE INCLINATION FOR SOLAR PANELS - Toshpulatova, Dildora; Narkulov, Saydulla (University Research Base, 2024)
The use of a tracking system to keep the PV cell/panel perpendicular to the sun can boost the collected energy by 10 - 100% depending on the circumstances. The use of a tracking system greatly improves the power gain from solar radiation. This background goes into further detail on the operation of solar cells and the reason tracking is needed. The different tracking technologies are also described and how they compare to one another. Different power applications require different tracking systems. For certain applications a tracking system is too costly and will decrease the max power that is gained from the solar panel. Due to the fact that the earth rotates on its axis and orbits around the sun, if a PV cell/panel is immobile, the absorption efficiency will be significantly less at certain times of the day and year.